The Power of Metaphor: Examining Its Influence on Social Life. 2014
DOI: 10.1037/14278-009
|View full text |Cite
|
Sign up to set email alerts
|

The metaphorical framing model: Political communication and public opinion.

Abstract: This chapter develops a comprehensive model of metaphor effects within the domain of political communication and political cognition. We begin by considering the nature and prevalence of metaphor commonly appearing in political rhetoric. We then provide an overarching theoretical perspective that conceptualizes metaphoric political rhetoric as a form of political framing. This metaphoric framing model posits that a communication or situational cue initially activates a root metaphor in the mind of the message … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Early demonstrations of metaphoric framing effects showed that messages comparing abstract topics to affectively charged sources changed target attitudes in source‐consistent directions (Ottati, Renstrom, & Price, ). Going beyond these direct effects, researchers reasoned that if metaphor creates a systematic conceptual mapping, then it should transfer personalized source knowledge (Ottati & Renstrom, ).…”
Section: But When Does Metaphor Shape Product Evaluation?mentioning
confidence: 99%
“…Early demonstrations of metaphoric framing effects showed that messages comparing abstract topics to affectively charged sources changed target attitudes in source‐consistent directions (Ottati, Renstrom, & Price, ). Going beyond these direct effects, researchers reasoned that if metaphor creates a systematic conceptual mapping, then it should transfer personalized source knowledge (Ottati & Renstrom, ).…”
Section: But When Does Metaphor Shape Product Evaluation?mentioning
confidence: 99%
“…Metaphors can explain a particular policy stance, persuade people toward a certain viewpoint, and affect people's opinion about policy issues (Bougher, 2012;Ottati et al, 2014). Metaphors were shown to help people to understand everyday issues and thereby affect people's choices about how to resolve given dilemmas (Robins & Mayer, 2000).…”
Section: Metaphorical Framing Effectsmentioning
confidence: 99%
“…A domain in which metaphors play an important role is political communication (e.g., Mio, 1997;Ottati et al, 2014). Metaphors can explain a particular policy stance, persuade people toward a certain viewpoint, and affect people's opinion about policy issues (Bougher, 2012;Ottati et al, 2014).…”
Section: Metaphorical Framing Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…By connoting similarities, both open and hidden, metaphors are important tools in the ideological conception of a phenomenon and in imposing a viewpoint. They therefore play a crucial role in the construction of social and political reality (Ottati et al., ). Metaphors make arguments seem more accurate and plausible.…”
Section: Methodsmentioning
confidence: 99%